Optogenetic stimulation of cholinergic fibers for the modulation of insulin and glycemia - Arjun K. Fontaine (Nature Portfolio, 2021)
Abstract Previous studies have demonstrated stimulation of endocrine pancreas function by vagal nerve electrical stimulation. While this increases insulin secretion, expected concomitant reductions in circulating glucose do not occur. A complicating factor is the non-specific nature of electrical nerve stimulation. Optogenetic tools, however, provide the potential for cell-type specific neural stimulation using genetic targeting and/or spatially shaped excitation light. Here, we demonstrate light-activated stimulation of the endocrine pancreas by targeting parasympathetic (cholinergic) axons. In a mouse model expressing ChannelRhodopsin2 (ChR2) in cholinergic cells, serum insulin and glucose were measured in response to (1) ultrasound image-guided optical stimulation of axon terminals in the pancreas or (2) optical stimulation of axons of the cervical vagus nerve. Measurements were made in basal-glucose and glucose-stimulated conditions. Significant increases in plasma insulin occurred relative to controls under both pancreas and cervical vagal stimulation, while a rapid reduction in glycemic levels were observed under pancreatic stimulation. Additionally, ultrasound-based measurements of blood flow in the pancreas were increased under pancreatic stimulation. Together, these results demonstrate the utility of in-vivo optogenetics for studying the neural regulation of endocrine pancreas function and suggest its therapeutic potential for the control of insulin secretion and glucose homeostasis.